Biomechanics of implant-supported prosthesis: A brief review (Research, Society and Development, 2023)
Objective: Perform a briel analysis of the biomechanics of implant-supported prostheses. Methodology: This study evaluated articles in databases; MEDLINE, SciELO, Lilacs and PubMed, with the descriptors: dental, implant, osseointegração, implanto-suportada, prótese. As the inclusion criteria were highlighted; clinical, laboratory articles, case reports that deepen their studies in the biomechanics and osseointegration of the dental implant. As the inclusion criteria were highlighted; clinical articles, laboratory, case reports that deepen their studies in the biomechanics and osseointegration of the dental implant were not used in very old articles that were not in the languages of English and Portuguese. Review of the literature and discussion: Through Branemark's research that dental implantation was possible through osseointegration and as a result of studies the implant-supported prosthesis, however failure may occur in this protocol due to several biological, chemical and mechanical factors. The occlusal force and overload is one of the main causes of these failures, having unique characteristics to be evaluated preoperatively, transoperatively and postoperatively avoiding the rapid absorption of bone support. With the help of technology you can avoid these overloads and monitor the stability of implants improving the lifetime of the implant-supported prosthesis. Final considerations: The forces applied during the implant protocol regarding the location and distribution of these forces requires a complex study with morphology and anatomy that resembles the preparation that will receive the primary implant for osseointegration, must present greater length and diameter respecting the characteristics of the patient, because the larger the area the lower the tension at the interface preventing failure of the implant-supported prosthesis.